2022
DOI: 10.17162/au.v13i1.1309
|View full text |Cite
|
Sign up to set email alerts
|

Investigación de los efectos de las actividades STEM en la actitud STEM en estudiantes superdotados

Abstract: El efecto de las actividades STEM en la actitud STEM de los estudiantes superdotados y el rendimiento STEM se examinaron en el presente estudio. Los participantes son 23 estudiantes superdotados que estudian en el Centro de Ciencias y Arte en el año académico 2020-2021. Las actividades se completaron en 54 horas lectivas en el marco del proceso de diseño de ingeniería. El método de la investigación se determinó como diseño mixto secuencial explicativo. Se utilizó un diseño experimental de grupo único como méto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Those educated through STEM are expected to exhibit 21st-century skills such as creative thinking, problem-solving, self-confidence, logical thinking, communication, using technology at a high level, competitiveness and critical thinking. STEM education uses a student-centred approach to provide learners with these skills (Kocaman, 2022;Stehle & Peters-Burton, 2019).…”
Section: Stem Educationmentioning
confidence: 99%
“…Those educated through STEM are expected to exhibit 21st-century skills such as creative thinking, problem-solving, self-confidence, logical thinking, communication, using technology at a high level, competitiveness and critical thinking. STEM education uses a student-centred approach to provide learners with these skills (Kocaman, 2022;Stehle & Peters-Burton, 2019).…”
Section: Stem Educationmentioning
confidence: 99%
“…At this point, multimodal representations provide teachers with many opportunities in order to meet these needs mentioned above as followings. Studies have shown that the dynamic activity results in important learning opportunities including learning disciplinary content knowledge and inquiry practices (Kocaman, 2022;Moro et al, 2019;Tang & Danielsson, 2018;Treagust et al, 2017;Tytler & Hubber 2016;Waldrip & Prain, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to Winberg et al (2019), STEM is a term that is more commonly used at the school level than in higher education, STEM is an educational model suitable for equipping gifted students with the necessary skills, developing creative and original solutions to problems, and directing them to STEM-related professions (Kocaman, 2023). STEM is a learning approach that is considered capable of building students' higher-order thinking skills (Hakim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In characterizing a particular research area, bibliometric analysis methods are used in a systematic review process that detects research patterns and current issues from previous publications (Nandiyanto et al, 2023). Recently, many reports on bibliometric analysis have been published to understand research trends on certain topics (Muhammad, Himmawan, et al, 2023;Muhammad, Marchy, et al, 2022, 2023Muhammad, Mukhibin, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%